The effect of education and 4-year experience in the evaluation of preanalytical process in a clinical chemistry laboratory - Medine Alpdemir; Mehmet Fatih Alpdemir; Zulfiye Akil (Medicine Science, 2018)
Preanalytical errors have an important ratios in all laboratory processes. To reduce laboratory errors, the IFCC working group on Laboratory Errors and Patient safety (WG-LEPS) developed laboratory quality indicators (QIs) for the preanalytical process. The purpose of this study is to evaluate QIs of the preanalytical process over a 4-year period and show the effect of education. In this study, Balikesir State Hospital biochemistry laboratory were retrospectively evaluated as rejected sample for four years (between 1st of January 2014 31st of December 2017). We examined QIs for preanalytical processes such as; misidentification errors (QIs-5), unintelligible test requests (QIs-6), lost-not received samples (QIs-7), incorrect container/tube (QIs-9), samples hemolyzed (QIs-10), sample clotted (QIs-11), insufficient sample volume (QIs-12), incorrect sample type (QIs-13, unsuitable transportation (QIs-14) and improperly labeled tube (QIs-15). In our hospital, regular training is given to hospital staff and laboratory staff at least twice a year for sample taking, specimen storage and transfer training, as well as laboratory staff, laboratory processes and management of improperly sample. In our study, the preanalytical process error frequency was 0.64%, 0.63%, 0.58% and 0.76% for all years respectively. It is seen that the most frequent error frequency is clotted sample (0.31, 0.32, 0.28 and 0.27 respectively). Other the most common errors was insufficient sample and incorrect container/tube (0.18, 0.15, 0.12, 0.07 and 0.18, 0.07, 0.07, 0.03, respectively). Our results were well below the optimum values recommended by IFFC-WG-LEPS. In order to achieve all these desired goals for QI, the training process must be sustainable and standardized and repeated at appropriate intervals. [Med-Science 2018; 7(4.000): 905-9]